Standardization of 18F-FDG–PET/CT According to Deauville Criteria for Metabolic Complete Response Definition in Newly Diagnosed Multiple Myeloma. Issue 2 (10th January 2021) - Zamagni, Elena; Nanni, Cristina; Dozza, Luca; Carlier, Thomas; Bailly, Clément; Tacchetti, Paola; Versari, Annibale; Chauvie, Stephane; Gallamini, Andrea; Gamberi, Barbara; Caillot, Denis; Patriarca, Francesca; et al.
Abstract : PURPOSE: 18 F-Fluorodeoxyglucose (FDG) positron emission tomography (PET)/computed tomography (CT) is currently the standard technique to define minimal residual disease (MRD) status outside the bone marrow (BM) in patients with multiple myeloma (MM). This study aimed to define criteria for PET complete metabolic response after therapy, jointly analyzing a subgroup of newly diagnosed transplantation-eligible patients with MM enrolled in two independent European randomized phase III trials (IFM/DFCI2009 and EMN02/HO95). PATIENTS AND METHODS: Two hundred twenty-eight patients were observed for a median of 62.9 months. By study design, PET/CT scans were performed at baseline and before starting maintenance (premaintenance [PM]). The five-point Deauville scale (DS) was applied to describe BM (BM score [BMS]) and focal lesion (FL; FL score [FS]) uptake and tested a posteriori in uni- and multivariable analyses for their impact on clinical outcomes. RESULTS: At baseline, 78% of patients had FLs (11% extramedullary), 80% with an FS ≥ 4. All patients had BM diffuse uptake (35.5% with BMS ≥ 4). At PM, 31% of patients had visually detectable FLs (2% extramedullary), 24% and 67.7% of them with an FS of 3 and ≥ 4, respectively. At PM, 98% of patients retained residual BM diffuse uptake, which was significantly lower than at baseline (mainly between BMS 2 and 3, BMS was ≥ 4 in only 8.7% of patients). By both uni- and multivariable analysis, FS and BMS < 4 were associated with prolonged progression-free survival (PFS) and overall survival (OS) at PM (OS: hazard ratio [HR], 0.6 and 0.47, respectively; PFS: HR, 0.36 and 0.24, respectively) CONCLUSION: FL and BM FDG uptake lower than the liver background after therapy was an independent predictor for improved PFS and OS and can be proposed as the standardized criterion of PET complete metabolic response, confirming the value of the DS for patients with MM.